Main determinants of fatherhood from the perspective of adolescent parentes - Ferreira, Danilo Fernandes (2024)
The objective of this literature review study is to verify the main determinants of paternity from the perspective of teenage fathers. Adolescence is the period of physical and psychological changes. The adolescent medicine has a vision of addressing multiple biological, psychological and social problems that affect health, thus providing the basis for a full attention. The adolescent pregnancy is considered a public health problem. This work emphasized the issue of paternity in adolescence from the viewpoint emphasizing individual who occupies the paternity. Concluding that the paternity in adolescence need to be included in welfare programs SUS along with the teenage motherhood, as well as the pregnant girl needs support, education and attention to their health, the boy must also receive the same attention to those programs that can together face this new phase of responsibility in their lives. Finally it is important to emphasize that the size of sexuality is not based on just the pursuit of sex and sexual activity, it encompasses the emotional feelings of the couple and mainly psychological and behavioral aspects of the culture of mankind.